2021
DOI: 10.1111/febs.15691
|View full text |Cite
|
Sign up to set email alerts
|

A tale of two proteins: PACT and PKR and their roles in inflammation

Abstract: I-like receptor signaling, as well as inflammasome activation. We go on to discuss the specific roles that PKR and PACT play in such proinflammatory signaling, as well as in metabolic syndrome-and environmental stress-induced inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 249 publications
(343 reference statements)
3
27
0
Order By: Relevance
“…The mechanisms by which PSMC3 variants activate PKR in NDD/ID affected individuals remain unclear, but our data open the possibility that PKR may sense a broader spectrum of danger signals than initially assumed, including perturbations of protein homeostasis. This concept is in line with the observation that activated PKR was found in the CNS of subjects with neurodegenerative diseases [8992] and that neurodegeneration is associated with neuroinflammation [93, 94]. Altogether, our work demonstrates that heterozygous PSMC3 dominant variants result in a neurodevelopmental syndrome associated with a specific type I IFN gene signature.…”
Section: Discussionsupporting
confidence: 90%
“…The mechanisms by which PSMC3 variants activate PKR in NDD/ID affected individuals remain unclear, but our data open the possibility that PKR may sense a broader spectrum of danger signals than initially assumed, including perturbations of protein homeostasis. This concept is in line with the observation that activated PKR was found in the CNS of subjects with neurodegenerative diseases [8992] and that neurodegeneration is associated with neuroinflammation [93, 94]. Altogether, our work demonstrates that heterozygous PSMC3 dominant variants result in a neurodevelopmental syndrome associated with a specific type I IFN gene signature.…”
Section: Discussionsupporting
confidence: 90%
“…ISGF3 translocates to the nucleus where it activates the transcription of IFN-stimulated genes (ISGs) ( 2 ). PKR is an ISG that binds to dsRNA and phosphorylates the α subunit of the eukaryotic initiation factor 2 (eIF2α) leading to general protein synthesis inhibition in order to restore cellular homeostasis upon viral infection ( 6 ). Moreover, it has been described that PKR interacts with several members of the TRAF family involved in MAVS signalling, such as TRAF2 and TRAF6 ( 7 ), and further contributing to the IFN response, it can also mediate phosphorylation of STAT1 ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…PACT, also known as PRKRA, a dsRNA-binding protein harboring three tandem repeats of dsRNA binding motifs, has initially been identified as a direct protein activator of PKR through their heterodimerization in response to diverse stress signals, leading to inhibition of protein translation ( Patel and Sen 1998 ; Patel et al 2000 ). Although PACT activation of PKR and its impact on proinflammatory response have been well documented ( Chukwurah et al 2021 ), more recent studies have also reported a negative regulatory role for PACT on PKR activation ( Clerzius et al 2013 ; Dickerman et al 2015 ; Meyer et al 2018 ). Phenotypic defects in PACT-deficient mice can be rescued by additional knockout of PKR or expression of a dominant-negative mutant of PKR, suggesting a primary function of PACT as a suppressor of aberrant PKR activation ( Dickerman et al 2015 ).…”
Section: Rna-binding Protein Partners Of Rna Sensorsmentioning
confidence: 99%
“…PKR is a dsRNA-activated serine–threonine kinase that plays a major role in a number of different cellular processes such as mRNA translation, transcriptional control, regulation of apoptosis, and proliferation (for reviews, see Gal-Ben-Ari et al 2018 ; Chukwurah et al 2021 ). Particularly, PKR is well-known for its role as a key innate immune sensor.…”
Section: Rna-binding Protein Partners Of Rna Sensorsmentioning
confidence: 99%